Stabilizacja za wszelką cenę? Negocjacje koalicyjne po wyborach parlamentarnych w 2005 roku - Zawiślak, Maciej (Polityka i Społeczeństwo, 2021)
The article presents the political situation in Poland after the 2005 Polish parliamen-tary elections and describes key points of the political program of Law and Justice, which was titled “Czwarta Rzeczpospolita”. The elections in 2005 were won by Law and Justice, a conservative party, who were led by Jarosław Kaczyński. Civic Platform occupied second place. Both parties wanted to cooperate in creating a majority coalition in the lower House of Parliament but the victory of Law and Justice and the troubled negotiations along with the triumph of Lech Kaczyński in the presidential election brought an end to the collaboration between these parties. The victorious party had to look for a partners to govern among the remaining parties. Eventually, the chiefs of Law and Justice decided to sign a stabilization pact with League of Polish Families and Self Defense Party. The agreement, signed in February 2006, did not bring about an end to the crisis of politics in Poland, therefore political leaders decided to announce an early election in 2007.